2003
DOI: 10.1086/377207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Comparison of True Methicillin-Resistant and Methicillin-Susceptible Coagulase-Negative Staphylococcal Bacteremia at Hospital Admission

Abstract: We performed 2 case-control studies among 108 patients with true coagulase-negative staphylococcal (CoNS) bacteremia diagnosed within 48 h of hospital admission. Seventy-nine patients (73%) with methicillin-resistant (MR) CoNS bacteremia and 29 patients (27%) with methicillin-susceptible (MS) CoNS bacteremia were compared with 79 randomly selected control patients without CoNS bacteremia. The presence of a central venous catheter was an independent risk factor for both MR- and MS-CoNS bacteremia (P<.001). Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
12
1
2
Order By: Relevance
“…Firstly, the investigation was restricted to meticillin-resistant CNS, as antimicrobial resistance is a marker for nosocomial strains, thereby excluding the possibility of detecting genetically closely related meticillin-sensitive CNS. 21 Secondly, the primary aim of the study was to detect putative clonal spread of CNS within the county hospital and not to evaluate the clinical relevance of analysed isolates. However, several clinically significant infections caused by multi-drug-resistant CNS were observed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the investigation was restricted to meticillin-resistant CNS, as antimicrobial resistance is a marker for nosocomial strains, thereby excluding the possibility of detecting genetically closely related meticillin-sensitive CNS. 21 Secondly, the primary aim of the study was to detect putative clonal spread of CNS within the county hospital and not to evaluate the clinical relevance of analysed isolates. However, several clinically significant infections caused by multi-drug-resistant CNS were observed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have documented that bloodstream infection caused by methicillin (meticillin)-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), extended-spectrum ␤-lactamase-producing Enterobacteriaceae, and multidrug-resistant Acinetobacter baumannii are associated significantly with mortality (7,9,11,24). Numerous papers have demonstrated that prior antimicrobial drug exposure is a strong risk factor for colonization and infection due to a drug-resistant pathogen (2,25,27). However, the association between antibiotic therapy and the acquisition of antibiotic-resistant bacteria (ARB) is still unclear and is often confounded by scarce data on antibiotic usage.…”
mentioning
confidence: 99%
“…Yeterli sayıda kan kültürü gönderilme-yen hastalarda, hastanın doktorunun ya da enfeksiyon kontrol ekibi doktorunun hastada sepsis bulgularının varlığını düşünmesi ve başka enfeksiyon odağının bulunmaması etkenin gerçek bakteriyemi etkeni olarak değerlendirilmesini sağladı. Çalışmamıza benzer şekilde daha önce yapılan farklı çalışmalarda, tek set kan kültüründe KNS üremesinin her zaman kontaminant olarak değerlendirilmemesi gerektiği bildirilmiş (9,10) ve bu nedenle CDC kriterlerinin klinik tanıdaki yerinin sorgulanması önerilmiştir.…”
Section: Discussionunclassified
“…Tacconelli ve ark. (9) çalışmalarında, santral venöz kateter varlığını hem metisiline dirençli KNS bakteriyemisi, hem de metisiline duyarlı KNS bakteriyemisi için risk faktörü olarak ortaya koymuşlardır.…”
Section: Elzi Ve Arkunclassified